Improving Creative Thinking Skills Through the PjBL-STEM Model assisted by LKPD Life Cycle Diology - Widiyono, Aan; Ghufron, Anik (Universitas Pendidikan Ganesha, 2024)
This study was motivated by the low creative thinking skills of students in elementary schools. This study aims to analyze the effect of the PjBL-STEM learning model assisted by Life Cycle Diology LKPD on students' creative thinking skills. This study used a quantitative approach with an experimental design (one group pretest-posttest design). The subjects of this study were 30 fifth-grade students who were selected using the saturated sample technique. Data were collected through essay tests that measured indicators of creative thinking skills, namely fluency, flexibility, originality, and elaboration. The research instrument used was an essay test. Data analysis was conducted through prerequisite tests (normality and homogeneity) and hypothesis testing with a t-test. This study found that applying the PjBL-STEM model assisted by Life Cycle Diology LKPD positively impacted student creative thinking skills development. The PjBL-STEM model provides a structured framework for students to combine knowledge from various disciplines, solve problems creatively, and produce original work. Thus, the PjBL-STEM learning model assisted by Life Cycle Diology LKPD effectively improves students' creative thinking skills. The implications of this study indicate that applying the PjBL-STEM model assisted by Life Cycle Diology LKPD effectively develops students' creative thinking skills, which are essential skills of the 21st century. This research significantly improves education quality through innovative and effective learning approaches.